2012
DOI: 10.1155/2012/714178
|View full text |Cite
|
Sign up to set email alerts
|

Facets of Parenting a Child with Hypoplastic Left Heart Syndrome

Abstract: The purpose of the study was to conceptualize the needs of parents of young children with hypoplastic left heart syndrome (HLHS) to provide a theoretical framework to inform the development of future parent interventions. Participants were parents and grandparents (n = 53) of 15 young children who had undergone the Sano surgical approach for HLHS. Analysis of recorded and transcribed single interviews with each participant was done as directed by interpretive description methodology. A model of five facets of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 56 publications
(56 reference statements)
1
55
0
Order By: Relevance
“…However, the evaluation of nursing discharge teaching and parents’ readiness for discharge among pediatric cardiology and cardiac surgery patients is not well described. Parenting children with congenital heart disease (CHD) is highly stressful for parents, both when their children are hospitalized and in the home setting (Rempel, Rogers, Ravindran, & Magill‐Evans, ), underscoring the importance of careful discharge planning.…”
mentioning
confidence: 99%
“…However, the evaluation of nursing discharge teaching and parents’ readiness for discharge among pediatric cardiology and cardiac surgery patients is not well described. Parenting children with congenital heart disease (CHD) is highly stressful for parents, both when their children are hospitalized and in the home setting (Rempel, Rogers, Ravindran, & Magill‐Evans, ), underscoring the importance of careful discharge planning.…”
mentioning
confidence: 99%
“…Rempel et al. () reported that mothers of infants with congenital heart anomalies experienced maternal anxiety due to possibility of death of the infant and an insufficient recovery from the life‐threatening nature of the anomaly (Rempel et al., ). When the future concerns of mothers of infants with CP‐CL anomalies were examined, it was observed that their primary concerns were speech problems (60.6%), irremediable physical appearance (21.2%), and an inability to fully recover from the disorder (12.1%).…”
Section: Discussionmentioning
confidence: 99%
“…Mothers of infants with congenital heart anomalies generally have fears such as not being able to fully recover from the disorder (40.6%), the inability of the infant to return to normal life (21.9%), inability of the infant to attend school (9.4%), inability to provide care for the infant due to insufficient income (9.4%), and fear of infant death (9.4%). The most significant fact mothers having infants with congenital heart anomaly have to face is reported to be a life-threatening disorder that will cause lifelong problems for the infant (Lawoko & Soares, 2002;Rempel, Rogers, Ravindran, & Magill-Evans, 2012). Rempel et al (2012) reported that mothers of infants with congenital heart anomalies experienced maternal anxiety due to possibility of death of the infant and an insufficient recovery from the life-threatening nature of the anomaly (Rempel et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Grandparent-provided child care (ie, babysitting, disease management, and respite care) is a vital source of support for parents raising children with a variety of chronic health conditions. [1][2][3][4][5] No previous research was found explicitly examining how GPs functionally or emotionally support their adult child parenting their grandchild diagnosed with type 1 diabetes (T1DM). Therefore, the purpose of this study was to explore the feasibility of using human patient simulation (HPS) to teach T1DM management and skills to GPs of young children (aged 12 and younger) diagnosed with T1DM ( Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are important, within the context of several related studies that have identified GPs as the most important source of secondary caregiving for parents of children with other, non-T1DM, chronic health conditions. [1][2][3] Understanding of and access to accurate information regarding their grandchild's chronic health condition is critical to a GP's involvement supporting their adult children parenting the child, as well as to the grandchild. 1 GP caregiving was significantly related to parents maintaining a positive emotional outlook and avoiding exhaustion 39 and was also associated with reduced maternal stress.…”
Section: Discussionmentioning
confidence: 99%